An Experience on Facts about Teaching Forensic Medicine to Undergraduate Medical Students in South Africa - B Meel (Institute of Medico-legal Publications Pvt Ltd, 2022)
South Africa is struggling with an enormous amount of forensic pathology services because there is an extreme pressure on forensic pathologists to deal with the high number of medicolegal autopsies in the country. There are only five dozen forensic pathologists in South Africa who have to handle at least 80 000 autopsies per year. Medical officers, who have only received training as undergraduates in medical school, are expected to conduct these autopsies. Therefore, undergraduate teaching and training must be strong enough so that these young graduates can handle cases without any compromise in the quality of the outcome.This report is going to highlight the necessity of teaching forensic medicine at undergraduate level in South African medical schools. It will also discuss the shortcomings in medical school teaching programmes.